Existence and Dynamics of The Islamic-Malay Sultanate Across The Malacca Strait: A Multifaceted Exploration Of Non-Western Ir Theories - Setiawan, Azhari (Review of International Relations (Jurnal Kajian Ilmu Hubungan Internasional), 2023)
The historical interactions among the Malay sultanates/kingdoms across the Malacca Strait offer a fascinating glimpse into the world of international relations beyond the Western lens. Based on the desire to build a non-Western IR theory, this study has highlighted the rich tapestry of cultural diversity, postcolonial struggles, local agency, alternative ideas, and hybridity that characterized the diplomatic landscape of these kingdoms. The struggle for power, strategic cooperation, and regionalism among the Malay kingdoms were deeply rooted in their cultural heritage, challenging the conventional narratives, and showcasing the resilience and adaptability of non-Western societies in shaping their international relations. As we reflect on these historical dynamics, it becomes evident that the lessons from the past continue to resonate in the contemporary global landscape, emphasizing the importance of embracing diverse perspectives and recognizing the agency of all nations in shaping the course of international relations. This study delves into the intricate historical interactions among the Islamic-Malay kingdoms in the Malacca Strait region. Employing a diverse array of non-Western International Relations (IR) theories, the research sheds light on the multifaceted dimensions of the diplomatic landscape in pre-modern Southeast Asia. Through an extensive library research approach, which involved the analysis of classic manuscripts and texts relevant to the topic, this study unveils the nuanced power struggles, strategic alliances, and regional cooperation mechanisms that shaped the Malay kingdoms’ international relations. By delving into these historical records, the research provides a comprehensive understanding of how cultural context, postcolonial perspectives, local agency, alternative ideas, and hybridity influenced the diplomatic maneuvers of the Malay kingdoms, challenging conventional Western-centric narratives and showcasing the richness of non-Western IR theories.